2017
DOI: 10.3389/fsoc.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

The Franciscan Prayer Elicits Empathic and Cooperative Intentions in Atheists: A Neurocognitive and Phenomenological Enquiry

Abstract: Religiosity influences the alleviation of troubles through cooperative and empathic attitudes, but these involve a sense of community offered in non-religious support groups and healthcare institutions too, where individual's spiritual well-being is based on responsibility and solidarity. This is the case of the Alcoholic Anonymous program adopted by several care initiatives, which use the Franciscan Prayer as a fundamental text representing a western epistemic meaning-making system to provide guidance for coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
(126 reference statements)
1
4
0
2
Order By: Relevance
“…We identified differentiated brain activations for each induced cognitive condition: reading was correlated to semantic process-related brain functions, introspection was correlated to self-reference process-related brain functions, and resting was correlated to a default neural network involved in anticipation of external events (see Section 4.6, Study 3). A particular interesting finding was the cerebellar activation while introspection, which agreed with previous studies about compassion reported in Mexico (Mercadillo et al, 2011;Mercadillo, Alcauter, et al, 2015;Mercadillo et al, 2017). Although cerebellar function is mainly related to motor processes, our results may suggest that this brain region allows an active introspective processes involving empathy and imagined motor actions.…”
Section: Integrative Discussion and Conclusionsupporting
confidence: 91%
See 2 more Smart Citations
“…We identified differentiated brain activations for each induced cognitive condition: reading was correlated to semantic process-related brain functions, introspection was correlated to self-reference process-related brain functions, and resting was correlated to a default neural network involved in anticipation of external events (see Section 4.6, Study 3). A particular interesting finding was the cerebellar activation while introspection, which agreed with previous studies about compassion reported in Mexico (Mercadillo et al, 2011;Mercadillo, Alcauter, et al, 2015;Mercadillo et al, 2017). Although cerebellar function is mainly related to motor processes, our results may suggest that this brain region allows an active introspective processes involving empathy and imagined motor actions.…”
Section: Integrative Discussion and Conclusionsupporting
confidence: 91%
“…Future studies correlating individual differences on morality and empathy with brain functions in extensive samples should be assessed. Also, phenomenological enquiries and ethnographic records to assess particular cultural contexts and experiences could be performed to relate individual subjectivity with brain function, as previously made in some studies (Mercadillo, Alcauter, et al, 2015; Mercadillo et al, 2017).…”
Section: Integrative Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results may support this assumption only for the ACC in men for whom it was connected with the IA, the IFG (affective component-associated brain regions), the dmPFC (related to mentalizing), and with other regions related to social and moral cognition, such as the frontal and temporal poles. As previously suggested, that ACC connectivity may allow regulation of empathic expressions (Kunz et al, 2011;Olalde-Mathieu et al, 2022) and its connectivity with the temporal pole may implicate autobiographical processes and the attribution of social qualities in others (Mercadillo et al, 2017). For women, the ACC was only coupled to the precuneus, whose function involves self-awareness related to emotional valuations, episodic memory (Ochsner et al, 2004;Atilano-Barbosa et al, 2022), imagery about another's mental states (Schurz et al, 2014) and moral judgments (Bzdok et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…DOI. https://doi.org/10.35600/25008870.2023.18.0295 330 funciones cerebrales que disponen a la empatía y la cooperación, aún en personas ateas, y que estas funciones disponen a la comprensión del otro y la responsabilidad social (Mercadillo et al, 2017). Así lo comprendimos al conocer que las experiencias sanadoras mediante hongos alucinógenos en la región Mazateca de Oaxaca, México, involucran saberes tradicionales profundos que desencadenan experiencias espirituales que pueden ser abiertamente dialogadas con las neurociencias para complementar el conocimiento de lo humano (Fagetti & Mercadillo, 2022).…”
Section: Comprensionesunclassified